RESPON BEBERAPA VARIETAS PADI SAWAH TERHADAP CARA APLIKASI PUPUK FOSFAT DI TANAH ALFISOL - ONGKO CAHYONO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
The objective of the research was to study the effect of the application method of phosphate fertilizer to the growth and yield of several rice varieties in Alfisol. This pot experiment was done at a glass house of Sumber Banjarsari Surakarta, at an elevation of about 100 meters above sea level from February till July 2015. This study was done under factorial design arranged in a completely randomized design involving two treatments, method of phosphate applications (six levels of treatments) and three rice varieties (IR54, Membramo and Pepe variety). The study concluded that the rice varieties used in this study (IR64, Membramo, Pepe) showed no different response to fertilizer application P. Fertilization P in the form of fast soluble P applied insplit application can save fertilizer to half the dose.